KAJIAN POTENSI DESA WISATA SEBAGAI PENINGKATAN EKONOMI MASYARAKAT DESA KARANG PATIHAN KECAMATAN BALONG 1 PONOROGO - Alip Sugianto (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2016)
Ponorogo is a region of East Java which has kind of potential tourisms, such as culture tourisms, natural tourisms, and craft industries which has spread out in many places. One of the places which has potential tourisms village is Karang Patihan subdistrict of which belongs to Balong Ponorogo. The Potention needs to be developed as one of the efforts to keep the culture, environmental lives and as alternative to increase economic society. This reaserch aims to identify the potention which has high values as the tourisms village. Thus, it can be known as original characters Karang Patihan Village in developing strategies of tourism village as the alternative increasing economic society.